Understanding Icy Worlds to Maximize Science Return on Future Missions. Issue 28 (15th July 2014) - Cable, Morgan L.; Beauchamp, Patricia M.; Senske, David
<x xml:space="preserve">Abstract</x> Missions to the outer planets are challenging. Far beyond the asteroid belt, the Sun is a weak source of energy—radioisotope thermoelectric generators (RTGs) tend to be the power system of choice over solar panels. The radiation environments can be extreme. Yet these icy worlds call to us. Some have icy plumes erupting into space; some are laden with organic material. All of the ingredients for life are there—water, chemistry, and energy—meaning that these planets could be livable environments.